2012
DOI: 10.1016/j.jfineco.2012.04.010
|View full text |Cite
|
Sign up to set email alerts
|

The effect of reference point prices on mergers and acquisitions

Abstract: a b s t r a c tPrior stock price peaks of targets affect several aspects of merger and acquisition activity. Offer prices are biased toward recent peak prices although they are economically unremarkable. An offer's probability of acceptance jumps discontinuously when it exceeds a peak price. Conversely, bidder shareholders react more negatively as the offer price is influenced upward toward a peak. Merger waves occur when high returns on the market and likely targets make it easier for bidders to offer a peak … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
248
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 359 publications
(278 citation statements)
references
References 67 publications
30
248
0
Order By: Relevance
“…The significance of 52-week high for our offer premiums is consistent with the recent findings of Baker, Pan, and Wurgler (2012). Moreover, offer premiums are higher for tender offers and when the acquirer is publicly traded.…”
Section: B Market Movements Over the Runup Periodsupporting
confidence: 90%
See 1 more Smart Citation
“…The significance of 52-week high for our offer premiums is consistent with the recent findings of Baker, Pan, and Wurgler (2012). Moreover, offer premiums are higher for tender offers and when the acquirer is publicly traded.…”
Section: B Market Movements Over the Runup Periodsupporting
confidence: 90%
“…Moreover, it is reasonable to assume that the signal is increasing in the size of the toehold. Also, we know from Baker, Pan, and Wurgler (2012) and Table IX below that the target's 52-week high return impacts the takeover premium.…”
Section: F2 Information Prior To the Runup Periodmentioning
confidence: 99%
“…This argument has been supported quite strongly by recent empirical research on financial markets: 1) Anchoring has been found to matter in the bank loan market as the current spread paid by a firm seems to be anchored to the credit spread the firm had paid earlier (see Douglas, Engelberg, Parsons, and Van Wesep (2015)). 2) Baker, Pan, and Wurgler (2012) provide evidence that peak prices of target firms become anchors in mergers and acquisitions.…”
Section: Anchoring and Adjustment Heuristic In Option Pricingmentioning
confidence: 99%
“…Both resources, process and management practices from these two firms can benefit each other as a result of M&A. (Baker et al, 2012) Nevertheless, the question remains the degree of integration. In other words, we want to keep the sound management practice of the target firm and unite that with the acquirer firm, while still remain efficient.…”
Section: Alternative Framework Of Mandamentioning
confidence: 99%